Head Master Strategy On Quality Of Learning At Babakanjati Cianjur Elementary School - Muhammad Fery Mustika; Khalid Ramdhani (ISLAMICA, 2020)
This research discusses the influence of Principal's Strategy on Quality of Learning at Babakanjati Cianjur Elementary School. The study was motivated by the important role of the principal in order to improve the quality of learning, because the movement of a school organization is controlled by a principal. The benefit of this research is theoretically able to contribute to the development of education management, especially education leadership. Practically of which is as an information material to Babakanjati Cianjur Elementary School in implementing the principal's management in improving the quality of learning. As an information material to other institutions about the implementation of leadership management, and for principals and teachers can be used as a reference in an effort to develop the quality and performance itself in the organization where the responsibility. The type of this research is qualitative research with descriptive analysis approach. This method is implemented as an effort to search for information deeply about the strategy that has been done by principal through interview and direct observation. The results show that the principal has performed his leadership well in accordance with his role and function as principal. Principal strategy in improving the quality of education at Babakanjati Cianjur Elemetary School based on education quality management.